2001
DOI: 10.1139/cjz-79-10-1822
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anoxia exposure and aerobic recovery on metabolic enzyme activities in the freshwater turtle <i>Trachemys scripta elegans</i>

Abstract: The effects of anoxic submergence (20 h at 7°C in nitrogen-bubbled water) and subsequent aerobic recovery (24 h at 7°C) on the maximal activities of 21 metabolic enzymes were assessed in liver, kidney, heart, brain, and red and white skeletal muscle of an anoxia-tolerant freshwater turtle, the red-eared slider, Trachemys scripta elegans. Anoxia exposure affected the activities of only a few enzymes; for example, it reduced the activity of phosphofructokinase in liver and brain, hexokinase in kidney, glycerol-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Previous studies have explored the importance of regulating glycolytic enzymes during anoxia exposure in T. s. elegans [9][11]. These studies have documented significant changes in both enzyme kinetics and activity upon prolonged exposure to anoxia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have explored the importance of regulating glycolytic enzymes during anoxia exposure in T. s. elegans [9][11]. These studies have documented significant changes in both enzyme kinetics and activity upon prolonged exposure to anoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Regulated liver enzymes involved in glycolysis include: phosphofructokinase (PFK), demonstrating a 3-fold decrease in the I 50 value for citrate and a 1.5-fold increase in the K m value for ATP during anoxia [9]; pyruvate kinase (PK), which demonstrated an anoxia responsive 1.5-fold increase in the I 50 for alanine and a 1.2-fold increase in maximal activity [9]; lactate dehydrogenase (LDH), displaying an increase in the K m value for pyruvate at various temperature and pH conditions, a decrease in the maximal activity (1.6-fold) in the lactate producing direction and a decrease in the I 50 for pyruvate at various temperature and pH conditions during exposure to anoxia [10]. Furthermore, a comprehensive study of 20 enzymes involved in intermediary metabolism showed multiple changes in activities due to prolonged exposure to anoxia [11]. These studies suggest that global control of glycolytic enzymes during bouts of anoxia seem to be paramount in the adaptation of T. s. elegans to anoxic stress.…”
Section: Introductionmentioning
confidence: 99%